FRI0323 Apremilast therapy in refractory skin lupus lesions. (12th June 2018) - Martín-Varillas, J.L.; Loricera, J.; Armesto, S.; Cuende, E.; Calvo-Río, V.; González-Vela, C.; Atienza-Mateo, B.; Hernández, J.L.; González-Gay, M.A.; Blanco, R.
Abstract : Background: Skin lesions of lupus may be refractory to standard therapy. Apremilast is an orally small molecule which inhibits phosphodiesterase-4 (PDE-4) that modulates some inflammatory pathways. Objectives: Our aim was to assess the efficacy of apremilast in lupus rashes refractory to conventional treatment. Methods: Retrospective study on 5 lupus patients treated with apremilast at standard dose of 30 mg twice daily. The outcome was improvement of lupus rashes. Results: We described 5 patients (4 women and 1 male) with a mean age of 44.2±8.5 years with extensive skin lesions due to lupus. Three patients had a discoid lupus and 2 patients had systemic lupus erythematosus (SLE) (one with panniculitis and the other with polycyclic ring lupus). The cutaneous lupus was confirmed in all patients by skin biopsy. Prior to apremilast all patients had received conventional treatment: topical corticosteroids (n=5), antimalarials (n=5), topical tacrolimus (n=2), oral corticosteroids (n=2), thalidomide (n=1), belimumab (n=1) and rituximab (n=1). After a mean follow-up of 6.2±2.9 months, all the patients experienced improvement of the skin lesions (in two patients was complete). In one patient it was necessary to reduce the dose of apremilast to 30 mg/day because of digestive symptoms. Conclusions: Apremilast can be useful in the treatment of refractory skin lesions of lupus. Disclosure of Interest: None declared